The energetic particle detector: energetic particle instrument suite for the Solar Orbiter mission - Rodriguez-Pacheco,J; Wimmer-Schweingruber,RF; Mason,GM; Ho,GC; Sanchez-Prieto,S; Prieto,M; Martin,C; Seifert,H; Andrews,GB; Kulkarni,SR; Panitzsch,L; Boden,S; et al. (Astronomy and Astrophysics: a European journal, 2020)
After decades of observations of solar energetic particles from space-based observatories, relevant questions on particle injection, transport, and acceleration remain open. To address these scientific topics, accurate measurements of the particle properties in the inner heliosphere are needed. In this paper we describe the Energetic Particle Detector (EPD), an instrument suite that is part of the scientific payload aboard the Solar Orbiter mission. Solar Orbiter will approach the Sun as close as 0.28 au and will provide extra-ecliptic measurements beyond ∼30° heliographic latitude during the later stages of the mission. The EPD will measure electrons, protons, and heavy ions with high temporal resolution over a wide energy range, from suprathermal energies up to several hundreds of megaelectronvolts/nucleons. For this purpose, EPD is composed of four units: the SupraThermal Electrons and Protons (STEP), the Electron Proton Telescope (EPT), the Suprathermal Ion Spectrograph (SIS), and the High-Energy Telescope (HET) plus the Instrument Control Unit that serves as power and data interface with the spacecraft. The low-energy population of electrons and ions will be covered by STEP and EPT, while the high-energy range will be measured by HET. Elemental and isotopic ion composition measurements will be performed by SIS and HET, allowing full particle identification from a few kiloelectronvolts up to several hundreds of megaelectronvolts/nucleons. Angular information will be provided by the separate look directions from different sensor heads, on the ecliptic plane along the Parker spiral magnetic field both forward and backwards, and out of the ecliptic plane observing both northern and southern hemispheres. The unparalleled observations of EPD will provide key insights into long-open and crucial questions about the processes that govern energetic particles in the inner heliosphere.